Electrolyte for zinc battery and zinc battery

JP7630919B2Active Publication Date: 2025-02-18ENERGYWITH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020085168
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-05-14
Publication Date
2025-02-18
Estimated Expiration
2040-05-14

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、サイクル寿命性能に優れる亜鉛電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630919000001
    Figure 0007630919000001
  • Figure 0007630919000002
    Figure 0007630919000002
Patent Text Reader

Abstract

To provide a zinc battery which is excellent in cycle life performance.SOLUTION: An electrolytic solution for a zinc battery contains an alkali metal hydroxide and at least one ion selected from the group consisting of bromide ions and iodide ions.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolyte for a zinc battery and to a zinc battery. [Background technology]

[0002] Known zinc batteries include nickel-zinc batteries, air-zinc batteries, and silver-zinc batteries. For example, nickel-zinc batteries are aqueous batteries that use an aqueous electrolyte such as an aqueous potassium hydroxide solution, and therefore are highly safe. In addition, the combination of zinc electrodes and nickel electrodes is known to provide a high electromotive force for an aqueous battery. Furthermore, nickel-zinc batteries have excellent input / output performance and low cost, and therefore their applicability to industrial applications (e.g., backup power sources, etc.) and automotive applications (e.g., hybrid vehicles, etc.) is being considered.

[0003] In zinc batteries, the discharge reaction produces zinc hydroxide (Zn(OH) 2 ) is generated. Zinc hydroxide is soluble in the electrolyte, and when zinc hydroxide dissolves in the electrolyte, it turns into zinc tetrahydroxide ions ([Zn(OH) 4 ] 2- ) diffuses into the electrolyte. As a result, the morphological change (deformation) of the negative electrode progresses and the distribution of the charging current becomes uneven, causing zinc to precipitate locally on the negative electrode, resulting in the formation of dendrites (branched crystals). In conventional zinc batteries, when dendrites grow due to repeated charging and discharging, they can penetrate the separator, causing a short circuit. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 58-126665 Summary of the Invention [Problem to be solved by the invention]

[0005] In the zinc batteries described above, there is a demand for improving the life performance (for example, cycle life performance).

[0006] Therefore, an object of the present invention is to provide a zinc battery having excellent cycle life performance. [Means for solving the problem]

[0007] One aspect of the present invention relates to an electrolyte for a zinc battery, which contains an alkali metal hydroxide and at least one ion selected from the group consisting of bromide ions and iodide ions.

[0008] According to the electrolyte of the above aspect, a zinc battery having excellent cycle life performance can be obtained.

[0009] In one embodiment, the electrolyte contains bromide ions, and in another embodiment, the electrolyte contains iodide ions.

[0010] The alkali metal hydroxide preferably includes potassium hydroxide.

[0011] The electrolyte preferably further contains ammonium ions.

[0012] The electrolyte is preferably for a nickel-zinc battery.

[0013] Another aspect of the present invention relates to a zinc battery comprising the above-mentioned electrolyte. Effect of the Invention

[0014] According to the present invention, a zinc battery having excellent cycle life performance can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] In this specification, the numerical range indicated by "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of a numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in an experimental example. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more types. In this specification, the amount of each component used in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. In this specification, the term "film" or "layer" includes a structure having a shape formed on the entire surface when observed as a plan view, as well as a structure having a shape formed on a part of the surface. In this specification, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended effect of the process is achieved.

[0016] Preferred embodiments of the present invention will be described below, however, the present invention is not limited to the following embodiments.

[0017] The electrolyte of one embodiment is an electrolyte for a zinc battery, for example, a basic (alkaline) electrolyte (also called an alkaline electrolyte). Here, the zinc battery is a battery (for example, an alkaline zinc battery) that uses a zinc electrode. Examples of the zinc battery include a nickel-zinc battery (for example, a nickel-zinc secondary battery) whose positive electrode is a nickel electrode; an air-zinc battery (for example, an air-zinc secondary battery) whose positive electrode is an air electrode; and a silver-zinc battery (for example, a silver-zinc secondary battery) whose positive electrode is a silver oxide electrode.

[0018] The electrolyte is a mixture of alkali metal hydroxide and bromide ions (Br - ) and iodide ion (I -) and at least one kind of ion selected from the group consisting of. The alkali metal hydroxide is dissolved in, for example, a liquid medium (for example, an aqueous liquid medium containing water such as ion-exchanged water) that is a solvent for the electrolyte. Therefore, it can be said that the electrolyte contains an alkali metal ion and at least one kind of ion selected from the group consisting of bromide ion and iodide ion. In addition, the bromide ion is, for example, an ion derived from an electrolyte that generates bromide ion by ionization (dissociation), and the iodide ion is, for example, an ion derived from an electrolyte that generates iodide ion by ionization (dissociation). Therefore, it can be said that the electrolyte contains an alkali metal hydroxide and at least one kind of electrolyte selected from the group consisting of an electrolyte that generates bromide ion by ionization and an electrolyte that generates iodide ion by ionization.

[0019] According to the above-mentioned electrolyte, a zinc battery having excellent cycle life performance can be obtained. The reason why such an effect is obtained is not clear, but the present inventors speculate as follows. First, in a zinc battery, a zinc passive film is formed on the surface of the zinc electrode as the battery reaction proceeds. It is considered that this passive film is one of the factors that deteriorates the cycle life performance, but when the above-mentioned electrolyte is used, the above-mentioned passive film is corroded by bromide ions and / or iodide ions in the electrolyte, so that it is considered that the thickening of the passive film is suppressed. As a result, it is speculated that the zinc battery using the electrolyte of the above-mentioned embodiment can suppress the deterioration of cycle life performance caused by the passive film, and can obtain excellent cycle life performance. In addition, the discharge characteristics are not deteriorated due to the presence of bromide ions and iodide ions, so that the above-mentioned electrolyte can achieve both excellent cycle life performance and sufficient discharge performance.

[0020] Examples of alkali metal hydroxides include potassium hydroxide (KOH), sodium hydroxide (NaOH), and lithium hydroxide (LiOH). In other words, examples of alkali metal ions contained in the electrolyte include potassium ions (K + ), sodium ion (Na + ), lithium ion (Li +From the viewpoint of excellent discharge performance, the alkali metal hydroxide preferably contains at least one selected from the group consisting of potassium hydroxide and lithium hydroxide, and more preferably contains potassium hydroxide. From the viewpoint of excellent discharge performance, the alkali metal ion preferably contains at least one selected from the group consisting of potassium ion and lithium ion, and more preferably contains potassium ion.

[0021] The content of alkali metal hydroxide in the electrolyte (total amount of alkali metal hydroxide) is preferably 10% by mass or more, and may be 15% by mass or more, 20% by mass or more, 25% by mass or more, or 30% by mass or more, based on the total mass of the electrolyte, from the viewpoint of excellent discharge performance. The content of alkali metal hydroxide in the electrolyte is preferably 50% by mass or less, and may be 45% by mass or less, 40% by mass or less, or 35% by mass or less, based on the total mass of the electrolyte, from the viewpoint of easily achieving both excellent life performance and excellent discharge performance.

[0022] The content of potassium hydroxide in the electrolyte is preferably 10% by mass or more, and may be 15% by mass or more, 20% by mass or more, 25% by mass or more, or 30% by mass or more, based on the total mass of the electrolyte, from the viewpoint of excellent discharge performance. The content of potassium hydroxide in the electrolyte is preferably 50% by mass or less, and may be 45% by mass or less, 40% by mass or less, or 35% by mass or less, from the viewpoint of easily achieving both excellent life performance and excellent discharge performance.

[0023] The content of lithium hydroxide in the electrolyte is preferably 0.1% by mass or more, and may be 0.3% by mass or more, 0.5% by mass or more, 0.8% by mass or more, or 1% by mass or more, based on the total mass of the electrolyte, from the viewpoint of excellent discharge performance. The content of lithium hydroxide in the electrolyte is preferably 3% by mass or less, and may be 2% by mass or less, 1.5% by mass or less, or 1.2% by mass or less, from the viewpoint of easily achieving both excellent life performance and excellent discharge performance.

[0024] The content (concentration) of the alkali metal ion in the electrolyte is preferably 5.0 mol / L or more, more preferably 6.0 mol / L or more, and even more preferably 7.0 mol / L or more, based on the total amount of the electrolyte, from the viewpoint of excellent discharge performance. The content (concentration) of the alkali metal ion in the electrolyte is preferably 10.0 mol / L or less, more preferably 9.0 mol / L or less, and even more preferably 8.0 mol / L or less, based on the total amount of the electrolyte, from the viewpoint of easily achieving both excellent life performance and excellent discharge performance.

[0025] The content (concentration) of potassium ions in the electrolyte is preferably 5.0 mol / L or more, more preferably 6.0 mol / L or more, and even more preferably 7.0 mol / L or more, based on the total amount of the electrolyte, from the viewpoint of excellent discharge performance. The content (concentration) of potassium ions in the electrolyte is preferably 10.0 mol / L or less, more preferably 9.0 mol / L or less, and even more preferably 8.0 mol / L or less, based on the total amount of the electrolyte, from the viewpoint of easily achieving both excellent life performance and excellent discharge performance.

[0026] The content (concentration) of lithium ions in the electrolyte is preferably 0.3 mol / L or more, more preferably 0.4 mol / L or more, and even more preferably 0.5 mol / L or more, based on the total amount of the electrolyte, from the viewpoint of excellent discharge performance. The content (concentration) of lithium ions in the electrolyte is preferably 0.8 mol / L or less, more preferably 0.7 mol / L or less, and even more preferably 0.6 mol / L or less, based on the total amount of the electrolyte, from the viewpoint of easily achieving both excellent life performance and excellent discharge performance.

[0027] The alkali metal ion may be, for example, an ion derived from an electrolyte that generates an alkali metal ion by ionization (dissociation) other than an alkali metal hydroxide. That is, in this embodiment, the electrolytic solution may further contain an electrolyte that generates an alkali metal ion by ionization other than an alkali metal hydroxide.

[0028] An example of an electrolyte that produces alkali metal ions upon ionization is potassium phosphate (K 3 PO4 ), potassium fluoride (KF), potassium carbonate (K 2 CO 3 ), Sodium phosphate (Na 3 PO 4 ), sodium fluoride (NaF), etc. In other words, the electrolyte may further contain phosphate ions, carbonate ions, fluoride ions, etc.

[0029] The electrolyte that generates an alkali metal ion upon ionization may be an electrolyte that generates an alkali metal ion and a bromide ion or an iodide ion upon ionization (alkali metal bromide or alkali metal iodide). Examples of the alkali metal bromide include potassium bromide (KBr), sodium bromide (NaBr), and lithium bromide (LiBr). Examples of the alkali metal iodide include potassium iodide (KI), sodium iodide (NaI), and lithium iodide (LiI).

[0030] The electrolyte may contain only one of bromide ions and iodide ions, or may contain both. From the viewpoint of further improving cycle life performance, it is preferable that the electrolyte contains bromide ions.

[0031] The bromide ion may be an ion derived from an electrolyte that generates a bromide ion by ionization other than an alkali metal bromide. Such an electrolyte includes, for example, ammonium bromide (NH 4 Br), calcium bromide (CaBr 2 ), Magnesium bromide (MgBr 2 ), phosphorus tribromide (PBr 3 ), phosphorus pentabromide (PBr 5 ), lead dibromide (PbBr 2 ), zinc bromide (ZnBr 2 ), Aluminum Bromide (AlBr 3 ), indium bromide (InBr 3 ), Tin Bromide (SnBr 2 ) etc.

[0032] As the electrolyte that generates bromide ions upon ionization, from the viewpoint of further improving cycle life performance, it is preferable to use at least one selected from the group consisting of alkali metal bromides and ammonium bromide, it is more preferable to use at least one selected from the group consisting of potassium bromide and ammonium bromide, and it is even more preferable to use ammonium bromide.

[0033] The content (concentration) of bromide ions in the electrolyte is preferably 0.01 mol / L or more, more preferably 0.05 mol / L or more, and even more preferably 0.1 mol / L or more, based on the total amount of the electrolyte, from the viewpoint of obtaining a better life performance. The content (concentration) of bromide ions in the electrolyte is preferably 0.5 mol / L or less, more preferably 0.4 mol / L or less, and even more preferably 0.3 mol / L or less, based on the total amount of the electrolyte, from the viewpoint of easily achieving both excellent life performance and excellent discharge performance.

[0034] The iodide ion may be an ion derived from an electrolyte that generates an iodide ion by ionization other than an alkali metal iodide. Examples of such electrolytes include ammonium iodide (NH 4 I), calcium iodide (CaI 2 ), Magnesium iodide (MgI 2 ), phosphorus triiodide (PI 3 ), phosphorus pentaiodide (PI 5 ), lead diiodide (PbI 2 ), zinc iodide (ZnI 2 ), Aluminum Iodide (AlI 3 ), indium iodide (InI 3 ), tin iodide (SnI 2 ) etc.

[0035] As the electrolyte that generates iodide ions through ionization, from the viewpoint of further improving cycle life performance, it is preferable to use at least one selected from the group consisting of alkali metal iodides and ammonium iodide, it is more preferable to use at least one selected from the group consisting of potassium iodide and ammonium iodide, and it is even more preferable to use ammonium iodide.

[0036] The content (concentration) of iodide ions in the electrolyte is preferably 0.01 mol / L or more, more preferably 0.05 mol / L or more, and even more preferably 0.07 mol / L or more, based on the total amount of the electrolyte, from the viewpoint of obtaining a better life performance. The content (concentration) of iodide ions in the electrolyte is preferably 0.5 mol / L or less, more preferably 0.4 mol / L or less, and even more preferably 0.3 mol / L or less, based on the total amount of the electrolyte, from the viewpoint of easily achieving both excellent life performance and excellent discharge performance.

[0037] The total content of bromide ions and iodide ions in the electrolyte is preferably 0.01 mol / L or more, more preferably 0.05 mol / L or more, even more preferably 0.07 mol / L or more, and particularly preferably 0.1 mol / L or more, based on the total amount of the electrolyte, from the viewpoint of obtaining a better life performance, and the total content of bromide ions and iodide ions in the electrolyte is preferably 0.5 mol / L or less, more preferably 0.4 mol / L or less, and even more preferably 0.3 mol / L or less, based on the total amount of the electrolyte, from the viewpoint of easily achieving both excellent life performance and excellent discharge performance.

[0038] The electrolyte contains ammonium ions (NH 4 + The ammonium ion is, for example, an ion derived from an electrolyte that generates an ammonium ion by ionization (dissociation). Examples of the electrolyte that generates an ammonium ion by ionization include ammonium bromide and ammonium iodide described above, as well as ammonium carbonate and ammonium nitrate.

[0039] The content (concentration) of ammonium ions in the electrolyte is preferably 0.01 mol / L or more, more preferably 0.05 mol / L or more, and even more preferably 0.1 mol / L or more, based on the total amount of the electrolyte, from the viewpoint of obtaining a better life performance. The content (concentration) of ammonium ions in the electrolyte is preferably 0.5 mol / L or less, more preferably 0.4 mol / L or less, and even more preferably 0.3 mol / L or less, based on the total amount of the electrolyte, from the viewpoint of easily achieving both excellent life performance and excellent discharge performance. The concentration of ammonium ions in the electrolyte may be 0.8 to 1.2 times the concentration of bromide ions in the electrolyte, may be 0.8 to 1.2 times the concentration of iodide ions in the electrolyte, or may be 0.8 to 1.2 times the sum of the concentrations of bromide ions and iodide ions in the electrolyte.

[0040] The electrolyte may further contain an organic compound containing oxygen atoms (hereinafter, sometimes referred to as "oxygen-containing compound"). When the electrolyte contains an oxygen-containing compound, the decrease in discharge capacity of the zinc battery due to repeated charging and discharging tends to be suppressed, and the decrease in discharge capacity during storage of the zinc battery can be suppressed, and excellent high-rate discharge performance tends to be obtained. These effects tend to be remarkable when an alkali metal hydroxide is used as the electrolyte.

[0041] The oxygen-containing compound may have a functional group containing an oxygen atom. Examples of the functional group containing an oxygen atom include a carboxyl group, a carboxylate group, a hydroxyl group (excluding OH structures included in the carboxyl group), an epoxy group, an ether group, an alkoxide group, an ester group, a ketone group, and an aldehyde group. From the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance, the oxygen-containing compound preferably has at least one selected from the group consisting of a carboxyl group, a carboxylate group, a hydroxyl group, an epoxy group, and an ether group.

[0042] When the oxygen-containing compound has an OH structure, the ratio of the number of OH structures to the number of carbon atoms in the oxygen-containing compound (number of OH structures / number of carbon atoms) is preferably within the following range from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance. The ratio is preferably 0.01 or more, 0.03 or more, 0.05 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 5 / 6 or more. The ratio is preferably 2 or less, 1.5 or less, 1.2 or less, 1 or less, 0.9 or less, or 5 / 6 or less. The oxygen-containing compound does not have to have an OH structure.

[0043] From the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance, it is preferable that the oxygen-containing compound contains at least one selected from the group consisting of sugars, carboxylic acids (excluding compounds corresponding to sugars), carboxylates (excluding compounds corresponding to sugars), epoxy compounds (compounds having an epoxy group; excluding compounds corresponding to sugars, carboxylic acids, or carboxylates), and ether compounds (compounds having an ether group; excluding compounds corresponding to sugars, carboxylic acids, carboxylates, or epoxy compounds).

[0044] The saccharides may be monosaccharides, disaccharides, trisaccharides, polysaccharides (excluding saccharides corresponding to disaccharides or trisaccharides), etc. Examples of monosaccharides include glucose, fructose, galactose, arabinose, ribose, mannose, xylose, sorbose, rhamnose, fucose, ribodesose, etc. Examples of disaccharides include maltose, trehalose, sucrose, cellobiose, gentiobiose, lactose, melibiose, etc. Examples of trisaccharides include raffinose, gentianose, melezitose, etc. Examples of polysaccharides include cyclodextrin (e.g., γ-cyclodextrin), stachyose, etc. The oxygen-containing compound preferably contains at least one selected from the group consisting of glucose, maltose, and raffinose, from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance.

[0045] Examples of the carboxylic acid include terephthalic acid, isophthalic acid, phthalic acid, benzoic acid, salicylic acid, 3,4,5-trihydroxybenzoic acid, benzenehexacarboxylic acid, formic acid, acetic acid, propionic acid, butyric acid, valeric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, aconitic acid, pyruvic acid, oxaloacetic acid, glycidyl formate, glycidyl acetate, and glycidyl benzoate. Examples of the carboxylate include salts of these carboxylic acids. Examples of the carboxylate include alkali metal salts such as sodium salts (e.g., disodium terephthalate) and potassium salts. The carboxylate preferably contains an alkali metal salt, and more preferably contains a sodium salt, from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance. From the viewpoint of easily suppressing the decrease in discharge capacity during storage of a zinc battery and easily obtaining excellent high-rate discharge performance, the oxygen-containing compound preferably contains at least one selected from the group consisting of carboxylic acids having aromatic rings and carboxylates having aromatic rings, more preferably contains at least one selected from the group consisting of terephthalic acid and terephthalic acid salts, and even more preferably contains at least one selected from the group consisting of terephthalic acid and sodium salts of terephthalic acid.

[0046] The number of carboxyl groups in the carboxylic acid or the number of carboxylate salts in the carboxylate is 1 or more, and from the viewpoint of easily suppressing a decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance, the following ranges are preferable: The number of carboxyl groups or carboxylate salts is preferably 2 or more; The number of carboxyl groups or carboxylate salts is preferably 4 or less, 3 or less, or 2 or less.

[0047] Examples of the epoxy compound include monofunctional epoxy compounds and polyfunctional epoxy compounds. Examples of the monofunctional epoxy compound include 1,2-epoxyethane, 1,2-epoxypropane, 1,2-epoxybutane, 1,2-epoxy-2-methylpropane, 1-phenyl-1,2-epoxyethane, epichlorohydrin, epibromohydrin, glycidyl methyl ether, allyl glycidyl ether, polyethylene oxide glycidyl ether, glycidyl amide, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, stearyl glycidyl ether, lauryl glycidyl ether, butoxy polyethylene glycol glycidyl ether, phenol polyethylene glycol glycidyl ether, allyl glycidyl ether, phenyl glycidyl ether, p-methylphenyl glycidyl ether, p-ethylphenyl glycidyl ether, p-sec-butylphenyl glycidyl ether, p-tert-butylphenyl glycidyl, glycidyl acrylate, and glycidyl methacrylate. Examples of the polyfunctional epoxy compound include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds, polyphenol type epoxy compounds, cyclic aliphatic epoxy compounds, aliphatic glycidyl ether type epoxy compounds, glycidyl ester type epoxy compounds, glycidyl diamine type epoxy compounds, heterocyclic epoxy compounds, cyclic aliphatic epoxy compounds, etc. The oxygen-containing compound preferably contains a monofunctional epoxy compound, more preferably contains 1,2-epoxy-2-methylpropane, from the viewpoint of easily suppressing the decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance.

[0048] Examples of the ether compound include crown ether compounds such as 18-crown-6, 15-crown-5, 12-crown-4, dibenzo-18-crown-6, dicyclohexano-18-crown-6, and dibenzo-24-crown-8; polyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; and glycerin. Examples of the ether compound include polyether compounds. From the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance, the oxygen-containing compound preferably contains an ether compound having a heterocycle containing an ether group, and more preferably contains 18-crown-6.

[0049] The number of ether groups in the ether compound is 1 or more, and from the viewpoint of easily suppressing a decrease in discharge capacity during storage of the zinc battery and easily obtaining excellent high-rate discharge performance, the following ranges are preferable: The number of ether groups is preferably 2 or more, 3 or more, 4 or more, 5 or more, or 6 or more; The number of ether groups is preferably 10 or less, 9 or less, 8 or less, 7 or less, or 6 or less.

[0050] The molecular weight of the oxygen-containing compound is preferably 50 or more, 70 or more, 80 or more, 100 or more, 120 or more, 150 or more, 160 or more, 170 or more, or 180 or more, from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. The molecular weight of the oxygen-containing compound is preferably 2000 or less, 1500 or less, 1300 or less, 1200 or less, 1000 or less, 800 or less, or 600 or less, from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. From these viewpoints, the molecular weight of the oxygen-containing compound is preferably 50 to 2000. The molecular weight of the oxygen-containing compound may be 190 or more, 200 or more, 210 or more, 220 or more, 240 or more, 260 or more, 300 or more, 340 or more, 350 or more, 400 or more, 450 or more, or 500 or more. The molecular weight of the oxygen-containing compound may be 500 or less, 400 or less, 350 or less, 340 or less, 320 or less, 300 or less, 280 or less, 270 or less, 260 or less, 250 or less, 230 or less, 220 or less, 210 or less, 200 or less, 190 or less, or 185 or less.

[0051] As the oxygen-containing compound, it is preferable to use a compound that is highly soluble in the electrolyte. Even if the compound is not highly soluble, it can be used by removing the residue by filtration, etc. The electrolyte according to the present embodiment does not need to contain alcohol.

[0052] The content of the oxygen-containing compound in the electrolyte is preferably in the following range based on the total amount of the electrolyte. The content of the oxygen-containing compound is preferably 0.1 mass% or more, 0.3 mass% or more, 0.5 mass% or more, 0.8 mass% or more, or 1 mass% or more from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. The content of the oxygen-containing compound is preferably 5 mass% or less, 4.5 mass% or less, 4 mass% or less, 3.5 mass% or less, or 3 mass% or less from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. From these viewpoints, the content of the oxygen-containing compound is preferably 0.1 to 5 mass%. The content of the oxygen-containing compound is preferably 1.2 mass% or more, 1.5 mass% or more, 1.8 mass% or more, 2 mass% or more, 2.2 mass% or more, 2.5 mass% or more, 2.7 mass% or more, or 3 mass% or more from the viewpoint of further easily suppressing the decrease in discharge capacity when the zinc battery is stored. The content of the oxygen-containing compound may be 3.5% by mass or more, 4% by mass or more, 4.5% by mass or more, or 5% by mass or more. From the viewpoint of easily obtaining even better high-rate discharge performance, the content of the oxygen-containing compound is preferably 2.7% by mass or less, 2.5% by mass or less, 2.2% by mass or less, 2% by mass or less, 1.7% by mass or less, 1.5% by mass or less, 1.2% by mass or less, or 1% by mass or less. The content of the oxygen-containing compound may be less than 0.5 mol / L based on the total amount of the electrolyte.

[0053] The content of the oxygen-containing compound is preferably in the following range relative to 100 parts by mass of the alkali metal hydroxide. The content of the oxygen-containing compound is preferably 1 part by mass or more, 1.5 parts by mass or more, 2 parts by mass or more, 2.5 parts by mass or more, or 3 parts by mass or more from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. The content of the oxygen-containing compound is preferably 30 parts by mass or less, 25 parts by mass or less, 20 parts by mass or less, 16 parts by mass or less, 15 parts by mass or less, 13 parts by mass or less, 12 parts by mass or less, or 10 parts by mass or less from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance. From these viewpoints, the content of the oxygen-containing compound is preferably 1 to 30 parts by mass. The content of the oxygen-containing compound is preferably 4 parts by mass or more, 5 parts by mass or more, 6 parts by mass or more, 7 parts by mass or more, 8 parts by mass or more, or 9 parts by mass or more from the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored. The content of the oxygen-containing compound may be 10 parts by mass or more, 12 parts by mass or more, 13 parts by mass or more, 15 parts by mass or more, or 16 parts by mass or more. From the viewpoint of easily obtaining further excellent high-rate discharge performance, the content of the oxygen-containing compound is preferably 9 parts by mass or less, 8 parts by mass or less, 7 parts by mass or less, 6 parts by mass or less, 5 parts by mass or less, or 4 parts by mass or less.

[0054] The electrolyte may contain an indium compound (a compound containing indium).By containing an indium compound in the electrolyte, the decrease in discharge capacity during storage of the zinc battery can be further suppressed, and for example, when the zinc battery is stored at 40°C for 7 days and then charged and discharged, the change in discharge capacity before and after storage can be further reduced.

[0055] Examples of the indium compound include indium sulfate, indium oxide, indium fluoride, indium chloride, indium bromide, indium iodide, indium nitrate, indium carbonate, etc. The indium compound preferably contains indium sulfate from the viewpoint of further suppressing the decrease in discharge capacity during storage of the zinc battery.

[0056] The content of the indium compound in the electrolyte is preferably within the following range based on the total amount of the electrolyte, from the viewpoint of further suppressing the decrease in discharge capacity during storage of the zinc battery. The content of the indium compound is preferably 0.01 mass% or more, 0.03 mass% or more, 0.05 mass% or more, 0.08 mass% or more, or 0.1 mass% or more. The content of the indium compound is preferably 2 mass% or less, 1.5 mass% or less, 1 mass% or less, 0.7 mass% or less, 0.5 mass% or less, 0.3 mass% or less, 0.2 mass% or less, or 0.1 mass% or less. From these viewpoints, the content of the indium compound is preferably 0.01 to 2 mass%.

[0057] The content of the indium compound is preferably in the following range with respect to 100 parts by mass of the alkali metal hydroxide, from the viewpoint of further suppressing the decrease in discharge capacity during storage of the zinc battery. The content of the indium compound is preferably 0.01 parts by mass or more, 0.03 parts by mass or more, 0.05 parts by mass or more, 0.1 parts by mass or more, 0.15 parts by mass or more, 0.2 parts by mass or more, 0.25 parts by mass or more, or 0.3 parts by mass or more. The content of the indium compound is preferably 10 parts by mass or less, 5 parts by mass or less, 3 parts by mass or less, 1 part by mass or less, 0.8 parts by mass or less, 0.5 parts by mass or less, 0.45 parts by mass or less, 0.4 parts by mass or less, or 0.35 parts by mass or less. From these viewpoints, the content of the indium compound is preferably 1 to 10 parts by mass.

[0058] The content of the indium compound is preferably in the following range with respect to 100 parts by mass of the oxygen-containing compound, from the viewpoint of further suppressing the decrease in discharge capacity during storage of the zinc battery. The content of the indium compound is preferably 0.1 parts by mass or more, 0.3 parts by mass or more, 0.5 parts by mass or more, 1 part by mass or more, 2 parts by mass or more, 3 parts by mass or more, 4 parts by mass or more, or 5 parts by mass or more. The content of the indium compound is preferably 20 parts by mass or less, 15 parts by mass or less, 10 parts by mass or less, 9 parts by mass or less, 8 parts by mass or less, 7 parts by mass or less, 6 parts by mass or less, or 5 parts by mass or less. From these viewpoints, the content of the indium compound is preferably 0.1 to 20 parts by mass.

[0059] The electrolyte may further contain other components such as zinc oxide, antimony oxide, titanium dioxide, and a surfactant.

[0060] Examples of the surfactant include a nonionic surfactant, an anionic surfactant, a cationic surfactant, and an amphoteric surfactant. From the viewpoint of easily suppressing the decrease in discharge capacity when the zinc battery is stored and from the viewpoint of easily obtaining excellent high-rate discharge performance, the surfactant preferably contains at least one selected from the group consisting of a nonionic surfactant, an anionic surfactant, and a cationic surfactant. The surfactant is preferably an embodiment containing a nonionic surfactant, preferably an embodiment containing an anionic surfactant, and preferably an embodiment containing a cationic surfactant.

[0061] The electrolyte solution of the above embodiment can be obtained, for example, by blending and mixing an alkali metal hydroxide, an electrolyte that generates bromide ions and / or iodide ions upon ionization, and, optionally, the above-mentioned optional components (an electrolyte other than an alkali metal hydroxide that generates alkali metal ions upon ionization, an electrolyte that generates ammonium ions upon ionization, an oxygen-containing compound, an indium compound, a surfactant, etc.) into a liquid medium that is a solvent.

[0062] In the above embodiment, an electrolyte that generates an alkali metal ion and a bromide ion and / or an iodide ion upon ionization may be used as the electrolyte that generates a bromide ion and / or an iodide ion upon ionization. Also, an electrolyte that generates a bromide ion and / or an iodide ion and an ammonium ion upon ionization may be used as the electrolyte that generates a bromide ion and / or an iodide ion upon ionization.

[0063] Hereinafter, a nickel-zinc battery will be described as an example of a zinc battery in which the electrolyte solution of the above embodiment is used.

[0064] The zinc battery of one embodiment includes a battery case, and an electrode group (e.g., an electrode plate group) and an electrolyte solution housed in the battery case. The zinc battery of one embodiment may be either formed or unformed.

[0065] The electrode group includes, for example, a positive electrode (for example, a positive electrode plate), a negative electrode (for example, a negative electrode plate), and a separator. The positive electrode and the negative electrode are adjacent to each other via one or more separators. That is, one or more separators are provided between adjacent positive electrodes and negative electrodes. The electrode group may include a plurality of positive electrodes, a plurality of negative electrodes, and a plurality of separators. When the electrode group includes a plurality of positive electrodes and / or a plurality of negative electrodes, the positive electrodes and the negative electrodes may be alternately stacked with the separators interposed therebetween. The plurality of positive electrodes and the plurality of negative electrodes may be connected to each other, for example, by a strap.

[0066] The positive electrode includes, for example, a positive electrode current collector and a positive electrode material supported on the positive electrode current collector.

[0067] The positive electrode current collector constitutes a conductive path for the current from the positive electrode material. The positive electrode current collector has, for example, a flat plate shape, a sheet shape, or the like. The positive electrode current collector may be a three-dimensional mesh-structured current collector constituted by foam metal, expanded metal, punching metal, felt-like material of metal fiber, or the like. The positive electrode current collector is constituted by a material having electrical conductivity and alkali resistance. For example, a material that is stable even at the reaction potential of the positive electrode (a material having an oxidation-reduction potential more noble than the reaction potential of the positive electrode, a material that forms a protective film such as an oxide film on the substrate surface in an alkaline aqueous solution to stabilize it, etc.) can be used as such a material. In addition, in the positive electrode, a decomposition reaction of the electrolyte proceeds as a side reaction, generating oxygen gas, and a material with a high oxygen overvoltage is preferable in that it can suppress the progress of such a side reaction. Specific examples of materials that constitute the positive electrode current collector include platinum; nickel; and metal materials (copper, brass, steel, etc.) plated with metals such as nickel.

[0068] The positive electrode material may be in a layered form (positive electrode material layer). For example, a positive electrode material layer may be formed on a positive electrode current collector, and when the positive electrode current collector has a three-dimensional mesh structure, the positive electrode material may be filled between the meshes of the positive electrode current collector.

[0069] The positive electrode material contains a positive electrode active material. Examples of the positive electrode active material include nickel oxyhydroxide (NiOOH) and nickel hydroxide. The positive electrode material contains, for example, nickel oxyhydroxide in a fully charged state and nickel hydroxide in an end-of-discharge state. The content of the positive electrode active material may be, for example, 50 to 95 mass% based on the total mass of the positive electrode material.

[0070] The positive electrode material may contain additives. Examples of additives include binders, conductive agents, and expansion inhibitors. Examples of binders include hydrophilic or hydrophobic polymers, such as hydroxypropylmethylcellulose (HPMC), carboxymethylcellulose (CMC), sodium polyacrylate (SPA), and fluorine-based polymers (polytetrafluoroethylene (PTFE)). The content of the binder may be, for example, 0.01 to 5 parts by mass relative to 100 parts by mass of the positive electrode active material. Examples of conductive agents include cobalt compounds (metallic cobalt, cobalt oxide, cobalt hydroxide, etc.). The content of the conductive agent may be, for example, 1 to 20 parts by mass relative to 100 parts by mass of the positive electrode active material. Examples of expansion inhibitors include zinc oxide. The content of the expansion inhibitor may be, for example, 0.01 to 5 parts by mass relative to 100 parts by mass of the positive electrode active material.

[0071] The negative electrode includes, for example, a negative electrode current collector and a negative electrode material supported on the negative electrode current collector.

[0072] The negative electrode current collector constitutes a conductive path for the current from the negative electrode material. The negative electrode current collector has, for example, a flat plate shape, a sheet shape, or the like. The negative electrode current collector may be a three-dimensional mesh-structured current collector constituted by foam metal, expanded metal, punching metal, felt-like material of metal fiber, or the like. The negative electrode current collector is constituted by a material having electrical conductivity and alkali resistance. For example, a material that is stable even at the reaction potential of the negative electrode (a material having an oxidation-reduction potential more noble than the reaction potential of the negative electrode, a material that forms a protective film such as an oxide film on the substrate surface in an alkaline aqueous solution to stabilize it, etc.) can be used as such a material. In addition, in the negative electrode, a decomposition reaction of the electrolyte proceeds as a side reaction to generate hydrogen gas, and a material with a high hydrogen overvoltage is preferable in that it can suppress the progress of such a side reaction. Specific examples of materials that constitute the negative electrode current collector include zinc; lead; tin; and metal materials (copper, brass, steel, nickel, etc.) plated with metals such as tin.

[0073] The negative electrode material may be in a layered form (negative electrode material layer). For example, the negative electrode material layer may be formed on a negative electrode current collector, and when the negative electrode current collector has a three-dimensional mesh structure, the negative electrode material may be filled between the meshes of the negative electrode current collector.

[0074] The negative electrode material contains a negative electrode active material containing zinc. Examples of the negative electrode active material containing zinc include metallic zinc, zinc oxide, zinc hydroxide, etc. For example, the negative electrode material contains metallic zinc in a fully charged state, and contains zinc oxide and zinc hydroxide in an end-of-discharge state.

[0075] The content of the negative electrode active material is preferably in the following range based on the total mass of the negative electrode material. From the viewpoint of easily achieving both excellent life performance and discharge performance, the content of the negative electrode active material is preferably 50 mass% or more, more preferably 70 mass% or more, and even more preferably 75 mass% or more. From the viewpoint of easily achieving both excellent life performance and discharge performance, the content of the negative electrode active material is preferably 95 mass% or less, more preferably 90 mass% or less, and even more preferably 85 mass% or less. From these viewpoints, the content of the negative electrode active material is preferably 50 to 95 mass%.

[0076] The negative electrode material may contain additives other than the negative electrode active material. Examples of the additives include a binder and a conductive agent. Examples of the binder include polytetrafluoroethylene, hydroxyethyl cellulose, polyethylene oxide, polyethylene, and polypropylene. The content of the binder may be, for example, 0.5 to 10 parts by mass relative to 100 parts by mass of the negative electrode active material. Examples of the conductive agent include an indium compound (such as indium oxide). The content of the conductive agent may be, for example, 1 to 20 parts by mass relative to 100 parts by mass of the negative electrode active material.

[0077] The separator may be, for example, a separator having a shape such as a flat plate or a sheet. Examples of the separator include a polyolefin-based microporous membrane, a nylon-based microporous membrane, an oxidation-resistant ion-exchange resin membrane, a cellophane-based regenerated resin membrane, an inorganic-organic separator, and a polyolefin-based nonwoven fabric. The separator may be processed into a bag shape so that the positive electrode and / or the negative electrode can be accommodated. In this case, the positive electrode and / or the negative electrode may be accommodated in the separator. The separator may be used alone or in combination of two or more types.

[0078] The manufacturing method of the nickel-zinc battery described above includes, for example, a component manufacturing process for obtaining components of the zinc battery, and an assembly process for assembling the components to obtain the zinc battery. In the component manufacturing process, at least electrodes (positive and negative electrodes) are obtained.

[0079] The electrodes can be obtained, for example, by adding a solvent (e.g., water) to raw materials of electrode materials (positive electrode material and negative electrode material) and kneading them to obtain an electrode material paste (a paste-like electrode material), and then forming an electrode material layer using the electrode material paste.

[0080] The raw materials for the positive electrode material include raw materials for the positive electrode active material (e.g., nickel hydroxide), additives (e.g., the binder), etc. The raw materials for the negative electrode material include raw materials for the negative electrode active material (e.g., metallic zinc, zinc oxide, and zinc hydroxide), additives (e.g., the indium compound and the binder), etc.

[0081] As a method for forming the electrode material layer, for example, an electrode material paste may be applied or filled onto a current collector, and then dried to obtain an electrode material layer. The density of the electrode material layer may be increased by pressing or the like, as necessary.

[0082] In the assembly process, for example, the positive and negative electrodes obtained in the component manufacturing process are alternately stacked with separators between them, and then the positive and negative electrodes are connected to each other with straps to form an electrode group. Next, this electrode group is placed in a battery case, and a lid is attached to the top of the battery case to obtain an unformed zinc battery (nickel-zinc battery).

[0083] Next, the electrolyte according to the present embodiment is poured into the battery case of the unformed zinc battery, and then left for a certain period of time. Then, the zinc battery (nickel-zinc battery) is obtained by forming the battery by charging under a predetermined condition. The forming conditions can be adjusted according to the properties of the electrode active materials (positive and negative active materials).

[0084] The above describes an example of a nickel-zinc battery (e.g., a nickel-zinc secondary battery) in which the positive electrode is a nickel electrode, but the zinc battery may also be an air-zinc battery (e.g., an air-zinc secondary battery) in which the positive electrode is an air electrode, or a silver-zinc battery (e.g., a silver-zinc secondary battery) in which the positive electrode is a silver oxide electrode.

[0085] The air electrode of the air zinc battery can be a known air electrode used in air zinc batteries. The air electrode includes, for example, an air electrode catalyst, an electron conductive material, etc. The air electrode catalyst can be an air electrode catalyst that also functions as an electron conductive material.

[0086] As the air electrode catalyst, one that functions as a positive electrode in an air zinc battery can be used, and various air electrode catalysts that can utilize oxygen as a positive electrode active material can be used. Examples of the air electrode catalyst include carbon-based materials (graphite, etc.) having an oxidation-reduction catalytic function, metal materials (platinum, nickel, etc.) having an oxidation-reduction catalytic function, and inorganic oxide materials (perovskite-type oxides, manganese dioxide, nickel oxide, cobalt oxide, spinel oxide, etc.) having an oxidation-reduction catalytic function. The shape of the air electrode catalyst is not particularly limited, and may be, for example, particulate. The amount of the air electrode catalyst used in the air electrode may be 5 to 70 volume % relative to the total volume of the air electrode, 5 to 60 volume %, or 5 to 50 volume %.

[0087] As the electron conductive material, a material that has electrical conductivity and enables electron conduction between the air electrode catalyst and the separator can be used. Examples of the electron conductive material include carbon blacks such as ketjen black, acetylene black, channel black, furnace black, lamp black, and thermal black; graphites such as natural graphite such as flake graphite, artificial graphite, and expanded graphite; conductive fibers such as carbon fibers and metal fibers; metal powders such as copper, silver, nickel, and aluminum; organic electron conductive materials such as polyphenylene derivatives; and any mixtures thereof. The shape of the electron conductive material may be particulate or may be other shapes. The electron conductive material is preferably used in a form that provides a continuous phase in the thickness direction in the air electrode. For example, the electron conductive material may be a porous material. The electron conductive material may also be in the form of a mixture or complex with the air electrode catalyst, and may be an air electrode catalyst that also functions as an electron conductive material as described above. The amount of the electronically conductive material used in the air electrode may be 10 to 80% by volume, 15 to 80% by volume, or 20 to 80% by volume relative to the total amount of the air electrode.

[0088] As the silver oxide electrode of the silver-zinc battery, a known silver oxide electrode used in silver-zinc batteries can be used. The silver oxide electrode includes, for example, silver(I) oxide. EXAMPLES

[0089] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.

[0090] <Preparation of electrolyte> Electrolyte solutions 1 to 5 were prepared by mixing ion-exchanged water, potassium hydroxide (KOH), lithium hydroxide (LiOH), and additives shown in Table 1 below in the amounts shown in Table 1. The amounts shown in Table 1 are based on the total mass of the electrolyte solution (unit: mass %). TrironX-100 manufactured by Sigma-Aldrich and RA-600 manufactured by Rhodafac were used as surfactants.

[0091] [Table 1]

[0092] <Example 1> [Preparation of positive electrode] A lattice body made of foamed nickel with a porosity of 95% was prepared, and the lattice body was pressure-molded to obtain a positive electrode current collector. Next, a predetermined amount of cobalt-coated nickel hydroxide powder, metal cobalt, cobalt hydroxide, yttrium oxide, CMC (carboxymethylcellulose), PTFE (polytetrafluoroethylene), and ion-exchanged water were weighed and mixed, and the mixture was stirred to prepare a positive electrode material paste. At this time, the mass ratio of the solid content was adjusted to "nickel hydroxide: metal cobalt: yttrium oxide: cobalt hydroxide: CMC: PTFE = 88: 10.3: 1: 0.3: 0.3: 0.1". The moisture content of the positive electrode material paste was adjusted to 27.5 mass% based on the total mass of the positive electrode material paste. Next, the positive electrode material paste was applied to the positive electrode material support part of the positive electrode current collector, and then dried at 80 ° C. for 30 minutes. After that, pressure molding was performed with a roll press to obtain an unformed positive electrode having a positive electrode material layer.

[0093] [Preparation of negative electrode] A tin-plated steel plate punching metal with an aperture ratio of 60% was prepared as a negative electrode current collector. Next, zinc oxide, metal zinc, HEC (hydroxyethyl cellulose) and ion-exchanged water were weighed and mixed in a predetermined amount, and the resulting mixture was stirred to prepare a negative electrode material paste. At this time, the mass ratio of the solid contents was adjusted to "zinc oxide:metal zinc:HEC=85:11.5:3.5". AV-15F (product name) manufactured by Sumitomo Seika Chemicals Co., Ltd. was used as the HEC. The moisture content of the negative electrode material paste was adjusted to 32.5 mass% based on the total mass of the negative electrode material paste. Next, the negative electrode material paste was applied onto the negative electrode current collector, and then dried at 80°C for 30 minutes. After that, it was pressure-molded by a roll press to obtain an unformed negative electrode having a negative electrode material (negative electrode material layer).

[0094] [Preparing the separator] For the separator, UP3355 (manufactured by Ube Industries, Ltd., product name, air permeability: 440 sec / 100 mL) was used as the microporous membrane, and nonwoven fabric (manufactured by Nippon Kodoshi Kogyo Co., Ltd., product name: VL-100, air permeability: 0.3 sec / 100 mL) was used as the nonwoven fabric. The microporous membrane was hydrophilized with a surfactant Triton-X100 (manufactured by Sigma-Aldrich Japan LLC) before the battery was assembled. The hydrophilization was performed by immersing the microporous membrane in an aqueous solution containing 1% by mass of Triton-X100 for 24 hours, and then drying at room temperature for 1 hour. The air permeability of the microporous membrane indicates the value after the hydrophilization. Furthermore, the microporous membrane was cut to a predetermined size, folded in half, and processed into a bag shape by heat welding the sides. The nonwoven fabric was cut to a predetermined size.

[0095] [Construction of nickel-zinc battery] A positive electrode (unformed positive electrode) and a negative electrode (unformed negative electrode) were housed in a microporous membrane processed into a bag shape. After laminating the positive electrode housed in the bag-shaped microporous membrane, the negative electrode housed in the bag-shaped microporous membrane, and the nonwoven fabric, the electrode plates of the same polarity were connected with a strap to prepare an electrode group (electrode plate group). The electrode group was configured with two positive electrodes and three negative electrodes, with one nonwoven fabric placed between each of the positive and negative electrodes (between the microporous membrane on the positive electrode side and the microporous membrane on the negative electrode side). After placing this electrode group in a battery case, a lid was attached to the top of the battery case, and the electrolyte 1 was poured into the battery case to obtain an unformed nickel-zinc battery. Thereafter, charging was performed under conditions of 32 mA and 15 hours to prepare a nickel-zinc battery with a nominal capacity of 320 mAh.

[0096] <Examples 2 to 4 and Comparative Example 1> Nickel-zinc batteries were fabricated in the same manner as in Example 1, except that electrolytic solution 1 was replaced with electrolytic solutions 2 to 5, respectively.

[0097] <Characteristics evaluation> The cycle life performance of the nickel-zinc batteries was evaluated using the nickel-zinc batteries of Examples 1 to 4 and Comparative Example 1. The specific evaluation method is shown below, and the results are shown in Table 2.

[0098] [Cycle life performance evaluation] The test consisted of charging the nickel-zinc battery at 25°C, 320mA (1C), and a constant voltage of 1.9V until the current value decayed to 16mA (0.05C), and then discharging the nickel-zinc battery at a constant current of 1280mA (4C) until the battery voltage reached 1.1V (one cycle). The test was terminated when the discharge capacity fell below 80% of the discharge capacity of the first cycle, and the cycle life performance was evaluated based on the number of cycles performed until the end of the test.

[0099] [Table 2]

Claims

1. The present invention relates to a method for producing an aqueous solution of an aqueous solution of an alkali metal hydroxide, at least one ion selected from the group consisting of a bromide ion and an iodide ion, and an organic compound having a hydroxyl group, An electrolyte for a zinc battery, wherein the organic compound having a hydroxyl group is a sugar.

2. 2. The electrolyte for a zinc battery according to claim 1, which contains bromide ions.

3. 3. The electrolyte for a zinc battery according to claim 1 or 2, which contains iodide ions.

4. The electrolyte according to any one of claims 1 to 3, wherein the alkali metal hydroxide comprises potassium hydroxide.

5. The electrolyte for zinc batteries according to any one of claims 1 to 4, further comprising ammonium ions.

6. The electrolyte according to any one of claims 1 to 5, which is for a nickel-zinc battery.

7. A zinc battery comprising the electrolyte solution according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Nickel-zinc battery

    CN111048846A

  • JP1974041833A

  • JP1974063934A

  • JP1974103139A

  • JP1975032437A